Polyether sulfone fiber, fiber package, nonwoven fabric, and manufacturing method of polyether sulfone fiber

JP2023051860A5Active Publication Date: 2025-03-12KB SEIREN LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022156283
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2022-09-29
Publication Date
2025-03-12
Estimated Expiration
2042-09-29

AI Technical Summary

Technical Problem

Polyether sulfone resins face challenges in being molded into fibers due to high viscosity, leading to difficulties in producing high-speed, high-purity fibers by melt spinning, and existing methods result in fibers with high heat shrinkage rates and poor dimensional stability.

Method used

A polyether sulfone fiber is produced using a resin with a specific chemical structure, spun without stretching, and processed under controlled melt-spinning conditions to achieve low dry heat shrinkage and excellent dimensional stability, mechanical strength, and flame retardancy.

Benefits of technology

The method produces fibers with low thermal shrinkage, high strength, and excellent dimensional stability, enabling their use in high-temperature environments and facilitating their processing into functional textile products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide: a polyether sulfone fiber which is formed by a melt-spinning method and has a low heat shrinkage, a good heat resistance, a low linear expansion coefficient, a large mechanical strength, a high fire retardancy, a high chemical resistance and a high dimensional stability; and a manufacturing method of the same.SOLUTION: A polyether sulfone fiber is composed of a polyether sulfone resin containing a repeating unit represented by a formula (1) as shown in the figure and has a dry-heat shrinkage of 5% or less at 200°C. The polyether sulfone resin has a glass-transition temperature (Tg) of 200°C or higher and may have a reduced viscosity ranging from 0.30 dl / g or more to 0.47 dl / g or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to polyethersulfone fibers, fiber packages, nonwoven fabrics, and methods for producing polyethersulfone fibers. [Background technology]

[0002] Polyethersulfone (hereinafter referred to as PES) has excellent heat resistance, creep resistance, dimensional stability, flame retardancy, and hot water resistance, and is being considered for use in a wide range of fields, including automotive parts, electronic parts, printer and copier parts, medical equipment parts that require sterilization, and dental equipment. For example, Patent Document 1 (JP-A-7-11134) describes an invention relating to a resin composition that uses a polyethersulfone as component (A), a polysulfone as component (B), and a polycarbonate resin as component (C) from among aromatic polysulfone resins, in which the respective proportions of the composition are 80 to 40% by weight for (A), 1 to 40% by weight for (B), and 1 to 40% by weight for (C).

[0003] Furthermore, Patent Document 2 (JP 2020-20053 A) describes an invention relating to a method for producing polyethersulfone fibers, in which polyethersulfone consisting of repeating units of a structure represented by a specific chemical formula and having an average weight molecular weight of 80,000 to 130,000 is dissolved in an organic solvent, a spinning solution having a polyethersulfone concentration of 10 to 30 mass % is discharged from a discharge hole into a spinning bath containing an organic solvent, and the resulting solution is stretched in wet heat at a magnification of 1.05 to 4 times.

[0004] Furthermore, Patent Document 3 (JP 3-185025 A) describes an invention relating to a method for producing aromatic polyethersulfone fibers, which comprises melting a polymer consisting of repeating units of predetermined chemical formulae I and II, where repeating units I and II are approximately equimolar and having a reduced viscosity of 0.3 or more as measured in NMP solvent at 30°C and a concentration of 0.5 g / dl at 30°C or higher, and melt-spinning the polymer into fibers at a take-up speed of 50 m / min or more from a spinneret having multiple spinning holes with diameters of 0.1 to 2.0 mm.

[0005] Patent Document 4 (China Patent Publication No. 1763278) describes polyethersulfone fibers and a manufacturing method thereof, in which the monofiber fineness is 0.3 to 30 dt, and the limiting oxygen index of the 1.5 to 10 dt fibers is 30 or more. The invention relates to a method for manufacturing polyethersulfone fibers in which a polyethersulfone resin is heated and melted in a twin-screw extruder, and then passed through a high-temperature resistant spinning pack again to flow in the form of a solution trickle, and then cooled and hardened to form fibers. Furthermore, Patent Document 5 (China Patent Application Publication No. 103361748) describes a high-temperature resistant polyethersulfone fiber and a manufacturing method thereof, and describes an invention relating to a manufacturing method of high-temperature resistant polyethersulfone fiber in which the water content is set to 50 ppm, melt spinning is performed at 330 to 380°C by twin-screw extrusion, and then cooling and hardening is performed to form the fiber. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 7-11134 [Patent Document 2] Japanese Patent Publication No. 2020-20053 [Patent Document 3] Japanese Patent Application Publication No. 3-185025 [Patent Document 4] Chinese Patent Application Publication No. 1763278 [Patent Document 5] Chinese Patent Application Publication No. 103361748 Summary of the Invention [Problem to be solved by the invention]

[0007] Although polyethersulfone resins have excellent physical properties such as heat resistance, dimensional stability, and flame retardancy, they have a problem in that they are difficult to mold into fibers due to their high viscosity when melted. In particular, it has been difficult to obtain high-purity fibers at high speed by melt spinning. Patent Document 1 discloses a technique for improving molding processability by mixing polyethersulfone with polycarbonate and melt molding the mixture, but does not mention the production of fibers.

[0008] Patent Document 2 describes the production of fibers from polyethersulfone resins. However, in Patent Document 2, polyethersulfone fibers are produced by wet spinning or dry spinning using a solvent, which requires a solvent in the production of fibers, and therefore there is a problem in that the solvent must be disposed of. Patent Document 3 describes a method for forming fibers from a polyethersulfone resin by melt spinning. However, Patent Document 3 also describes that fibers can be formed by melt spinning by using an aromatic polyethersulfone resin having a specific structure. In this case, no solvent is required, but since it is necessary to use copolymerized polyethersulfone containing a special repeating unit, there is a problem that it is difficult to obtain the raw material.

[0009] Patent Document 4 describes that polyethersulfone monofilaments can be provided by adjusting the temperature setting of an extruder when melt-extruding a polyethersulfone resin, and then performing a drawing treatment after melt spinning. In this case, because the drawing treatment is performed with a strong drawing force to obtain fibers, the obtained fibers have a high heat shrinkage rate, which limits the applications in which they can be used. Furthermore, the high-temperature resistant polyethersulfone fiber of Patent Document 5 also uses a modified masterbatch as a raw material and is stretched 2.3 to 6 times, which means that the raw material is special, the thermal shrinkage is high, and there are problems with dimensional stability.

[0010] In the field of industrial materials, heat resistance and dimensional stability are particularly required. To achieve both heat resistance and dimensional stability, it is important to reduce the dry heat shrinkage. However, the polyethersulfone fibers obtained by the methods described in Patent Documents 4 and 5 have the problem of high heat shrinkage, but neither of these documents mentions the dry heat shrinkage.

[0011] Furthermore, because polyethersulfone resin is an amorphous thermoplastic resin, it has a high melt viscosity and is prone to melt fracture (roughening of the fiber surface), making it difficult to stably produce polyethersulfone fiber. Even if it were possible to produce it, the fiber would have insufficient quality or physical properties, resulting in poor processability in subsequent processes such as fiber processing.

[0012] The present invention aims to solve the above-mentioned problems and to provide a polyethersulfone fiber produced by a melt spinning method, which has a small heat shrinkage rate and excellent heat resistance, a low coefficient of linear expansion, mechanical strength, flame retardancy, chemical resistance and dimensional stability, and a method for producing the same. Another object of the present invention is to provide a polyethersulfone fiber that can be melt-spun using a polyethersulfone resin with a simple structure, is environmentally friendly, and is cost-effective, and has high purity, as well as a method for producing the same. A further object of the present invention is to provide a polyethersulfone fiber having high strength, little variation in strength, and excellent tensile elongation, and a method for producing the same. A further object of the present invention is to provide a polyethersulfone fiber which has excellent dimensional stability, good post-processability, and excellent processability. [Means for solving the problem]

[0013] (1) According to one aspect, the polyethersulfone fiber is made of a polyethersulfone resin containing a repeating unit represented by the following formula (1), and has a dry heat shrinkage at 200°C of 5% or less. [ka]

[0014] According to the present invention, polyethersulfone having excellent heat resistance, a low coefficient of linear expansion, mechanical strength, flame retardancy, chemical resistance, and dimensional stability can be used to produce fibers, and in particular, even when a melt spinning method is used, the fibers do not need to be stretched, so polyethersulfone fibers that hardly experience thermal shrinkage can be obtained. In other words, the reason why conventional PES fibers experience heat shrinkage is thought to be because PES resin is an amorphous resin that is difficult to mold, and the molecules are stretched when the fiber is stretched, which causes entropy shrinkage and fiber shrinkage in high-temperature environments above 100°C. On the other hand, the PES fiber of the present invention is an unstretched PES fiber, so its dry heat shrinkage can be kept extremely low. This allows for a fiber that has excellent dimensional stability and maintains high strength with little strength variation even in high-temperature environments. Furthermore, because the fiber has excellent dimensional stability and tensile elongation, it is easily passable through subsequent processes and has excellent processability as a fiber, making it suitable for use in high-performance textile products. Furthermore, since it can be spun using a polyethersulfone resin with a simple structure and can be produced into fiber at a relatively low temperature by a melt spinning method that does not require solvent recovery, etc., no special spinning equipment is required, and polyethersulfone fibers can be produced that are excellent in terms of the environment and cost. Furthermore, since no solvent is used in the spinning process, the content of impurities can be significantly reduced, resulting in high-performance fibers. In the present invention, the polyethersulfone fiber made of polyethersulfone resin may contain additives or mixtures to the extent that the additives or mixtures do not impair the physical properties.

[0015] (2) In the polyethersulfone fiber according to one aspect of the second invention, the polyethersulfone resin may contain 95 mol % or more of the repeating unit represented by formula (1). More preferably, the polyethersulfone resin contains 98 mol % or more, and most preferably 100 mol % of the repeating unit represented by formula (1).

[0016] This allows for the production of polyethersulfone resin, which has a simple structure and is easily available, and therefore does not require special spinning equipment, making it possible to produce polyethersulfone fibers that are superior in terms of the environment and cost.

[0017] (3) The polyethersulfone fiber according to a third aspect of the present invention is the polyethersulfone fiber according to the first aspect or the second aspect of the present invention, wherein the polyethersulfone resin has a glass transition temperature (Tg) of 200°C or higher and a reduced viscosity of 0.30 dL / g or higher and 0.47 dL / g or lower.

[0018] This allows the polyethersulfone fiber to have excellent winding properties after spinning and excellent post-processability.

[0019] (4) The polyethersulfone fiber according to a fourth aspect of the present invention is the polyethersulfone fiber according to any one of the first to third aspects of the present invention, and may have at least one physical property selected from the group consisting of the following physical properties (A), (B), and (C): Physical property (A): The breaking strength of the polyethersulfone fiber is 0.6 cN / dtex or more. Physical property (B): The breaking strength variation of the polyethersulfone fiber is within ±0.3 cN / dtex Physical property (C): The elongation of the polyethersulfone fiber is 10% or more and less than 200%.

[0020] This makes it possible to obtain polyethersulfone fibers that are even stronger and more uniform in strength, and also have excellent properties such as dimensional stability and thermal stability. Furthermore, since the tensile elongation is also superior, the fibers are also more easily processable as fibers, and can be easily used as high-performance fiber products.

[0021] (5) The polyethersulfone fiber according to the fifth aspect of the present invention is the polyethersulfone fiber according to the fourth aspect of the present invention, and in the physical property (A), the polyethersulfone fiber may have a breaking strength of 1.0 cN / dtex or more.

[0022] This allows for the production of polyethersulfone fibers with even higher strength and excellent properties such as dimensional stability and thermal stability. Furthermore, even with high strength, the fibers have excellent tensile elongation and almost no variation in strength, making them excellent in post-processability. For example, when processed into nonwoven fabrics, processes such as filament cutting can be easily carried out.

[0023] (6) The fiber package according to the sixth aspect of the present invention may be such that the polyethersulfone fiber according to any one of the first to fifth aspects of the present invention is wound around a tube.

[0024] This makes the polyethersulfone fiber easier to handle and provides excellent processability as a fiber product.

[0025] (7) The nonwoven fabric according to the seventh aspect of the present invention may contain the polyethersulfone fiber according to any one of the first to fifth aspects of the present invention.

[0026] This makes it possible to obtain a highly functional, low-cost nonwoven fabric that is excellent in heat resistance, dimensional stability, low dry heat shrinkage, and strength.

[0027] (8) A method for producing a polyethersulfone fiber according to another aspect includes a drying step of drying a polyethersulfone resin to obtain a dried polyethersulfone resin, a melting step of heating and melting the dried polyethersulfone resin to obtain a molten material, a spinning step of extruding the molten material from a spinneret to form spun yarns, a bundling step of focusing the spun yarns to obtain filaments, and a winding step of winding the filaments, and satisfies the following conditions: Condition (a): The moisture content of the dried polyethersulfone resin is less than 50 ppm Condition (b): Linear velocity of discharge is 5.0 m / min or more and 50.0 m / min or less Condition (c): Shear rate during spinning is 300 s -1 More than 90,000s -1 below Condition (d): Spinning temperature is 340°C or higher and 410°C or lower Condition (e): Winding speed is 550 m / min or more

[0028] According to the present invention, a polyethersulfone resin having excellent heat resistance, a low coefficient of linear expansion, mechanical strength, flame retardancy, chemical resistance, and dimensional stability can be used to produce a fiber. In particular, even when a melt spinning method is used, the fiber does not need to be stretched, so that a polyethersulfone fiber that hardly undergoes thermal shrinkage can be obtained. In other words, the reason why conventional PES fibers experience heat shrinkage is thought to be because PES resin is an amorphous resin that is difficult to mold and process, and the molecules are stretched when the fiber is stretched. As a result, entropy shrinkage occurs, causing the fiber to shrink in high-temperature environments exceeding 100°C. On the other hand, the manufacturing method of the present invention is characterized by not performing a post-processing step in which bundled filaments are heated and stretched. This allows the dry heat shrinkage to be kept extremely low, thereby producing a fiber that has excellent dimensional stability, maintains high strength, and has little strength variation, even in high-temperature environments. Furthermore, because the fiber has excellent dimensional stability and tensile elongation, it is easily passable through post-processing processes and has excellent processability as a fiber, making it suitable for use in high-performance textile products. Furthermore, since the polyethersulfone fiber can be produced at a relatively low temperature by a melt spinning method that does not require solvent recovery, etc., no special spinning equipment is required, and the polyethersulfone fiber is excellent in terms of the environment and cost. Furthermore, since no solvent is used in the spinning process, the content of impurities can be significantly reduced, resulting in a high-performance fiber.

[0029] (9) A ninth aspect of the present invention relates to a method for producing a polyethersulfone fiber, which is the method for producing a polyethersulfone fiber according to the eighth aspect of the present invention, and which further includes the step of: (i) dissolving the polyethersulfone resin in a polyethersulfone fiber; (ii) dissolving the polyethersulfone resin in a polyethersulfone fiber; (iii) dissolving the polyethersulfone resin in a polyethersulfone fiber; and (iv) dissolving the polyethersulfone resin in a polyethersulfone fiber;

[0030] This makes it difficult for thread breakage to occur and prevents the filtration pressure from becoming too high, resulting in excellent spinnability and ensuring reliable winding of the fiber.

[0031] (10) A tenth aspect of the present invention relates to a method for producing a polyethersulfone fiber according to the eighth or ninth aspect of the present invention, wherein the spinning temperature in condition (d) is 340°C or higher and 385°C or lower.

[0032] This allows for the production of polyethersulfone fibers with even higher strength and excellent properties such as dimensional stability and thermal stability. Furthermore, even with high strength, the fibers have excellent tensile elongation and almost no variation in strength, making them excellent in post-processability. For example, when processed into nonwoven fabrics, processes such as filament cutting can be easily carried out. [Brief explanation of the drawings]

[0033] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of a method for producing polyethersulfone fibers by melt-extruding and melt-spinning a polyethersulfone resin. DETAILED DESCRIPTION OF THE INVENTION

[0034] The present invention will be described in detail below. In the present invention, by using a polyethersulfone resin having a specific chemical structure as a raw material and appropriately selecting the melt spinning conditions, it is possible to produce a fiber without stretching during the production process, which results in a polyethersulfone fiber with an extremely small heat shrinkage rate and excellent heat resistance, a low coefficient of linear expansion, mechanical strength, flame retardancy, chemical resistance, and dimensional stability. In particular, because PES resin is an amorphous resin, it has high viscosity when melted and is prone to melt fracture (roughening of the fiber surface), making it difficult to mold. For this reason, it has traditionally been difficult to produce PES fiber from PES resin using the melt spinning method. When PES resin is turned into fiber using the melt spinning method, stable production is difficult, and the resulting fiber has a high thermal shrinkage rate and poor dimensional stability. This is thought to be because the fiber molecules are stretched by the drawing process after spinning, and when the PES fiber is exposed to a high-temperature environment exceeding 100°C, entropy contraction occurs, causing the fiber to thermally shrink. The PES fiber of the present invention is an undrawn PES fiber, and therefore its dry heat shrinkage can be kept extremely low. This allows for a fiber that has excellent dimensional stability even in high-temperature environments, maintains high strength, and has little strength variation. Furthermore, because it has excellent tensile elongation, it is easy to pass through subsequent processes and has excellent processability as a fiber, making it suitable for use in high-performance textile products. Furthermore, the PES fiber of the present invention can be spun using a polyethersulfone resin with a simple structure, and can be produced by a melt spinning method that does not require solvent recovery, etc., so that no special spinning equipment is required, making it an excellent PES fiber from the standpoints of the environment and cost. Furthermore, because no solvent is used in the spinning process, the impurity content can be significantly reduced, resulting in a high-performance fiber.

[0035] [Polyethersulfone resin] The polyethersulfone resin used in the present invention contains specific polyethersulfone structural units and satisfies predetermined properties, and therefore has a good balance between moldability, heat resistance, and low thermal shrinkage. The polyethersulfone fiber of the present invention is made of the following polyethersulfone resin, and the polyethersulfone resin mainly contains a repeating unit represented by the following formula (1). [ka]

[0036] (Structural unit of polyethersulfone resin) The repeating unit of formula (1) is described in detail below. The content of the repeating unit of formula (1) in all repeating units constituting the polyethersulfone resin is preferably 95 mol % or more. From the viewpoint of improving heat resistance, the mol % is preferably 98 mol % or more, more preferably 99 mol % or more, and most preferably 100 mol %.

[0037] There are no particular restrictions on the terminal structure of the polyethersulfone resin, but it is preferable that the polyethersulfone resin has a chain aliphatic group having 5 to 14 carbon atoms at the terminal. The chain aliphatic group may be saturated or unsaturated, and may be straight-chain or branched.

[0038] The polyethersulfone resin of the present invention is characterized by high heat resistance, strong mechanical properties, chemical resistance, and hydrolysis resistance. Furthermore, since it does not contain bonds that are easily hydrolyzed, such as ester bonds, it has excellent hot water resistance and can be used in high-temperature steam atmospheres. Furthermore, it has a small coefficient of linear expansion and its temperature dependency is small, resulting in excellent dimensional stability.

[0039] (Conditions for polyethersulfone resin) The polyethersulfone resin used in the present invention preferably satisfies the following properties (a) and (b). Property (a): Glass transition temperature (Tg) of 200°C or higher Characteristic (b): Reduced viscosity is 0.30 dl / g or more and 0.47 dl / g or less

[0040] By satisfying the above properties (a) and (b), polyethersulfone resins have a good balance between spinnability and heat resistance. Because polyethersulfone resins are prone to shear heating during molding, properties (a) and (b) affect the spinning conditions. Therefore, polyethersulfone resins that satisfy both properties (a) and (b) also have good spinnability.

[0041] Regarding the property (a), the glass transition temperature (Tg) of the polyethersulfone resin is preferably 200°C or higher, more preferably 210°C or higher, and even more preferably 220°C or higher, from the viewpoint of heat resistance, and is preferably 250°C or lower, more preferably 240°C or lower, and even more preferably 230°C or lower, from the viewpoint of achieving high spinnability. If the glass transition temperature (Tg) of the polyethersulfone resin is less than 200°C, the heat resistance tends to be low and insufficient. The glass transition temperature (Tg) of a polyethersulfone resin can be measured by the following method: Using differential scanning calorimetry (DSC), the temperature is raised from 30°C to a temperature at least 30°C higher than the predicted glass transition temperature at a heating rate of 10°C / min, held for 1 minute, then cooled to 0°C at a cooling rate of 20°C / min, held for 1 minute, and then measured again at a heating rate of 10°C / min to measure the observed glass transition temperature (Tg).

[0042] Regarding property (b), the reduced viscosity of the polyethersulfone resin used in the fiber of the present invention is preferably 0.30 dL / g or more, more preferably 0.33 dL / g or more, and most preferably 0.35 dL / g or more, and is preferably 0.47 dL / g or less, more preferably 0.45 dL / g or less, and most preferably 0.44 dL / g or less. If the reduced viscosity exceeds the upper limit, the spinnability tends to be poor in the melt spinning step.

[0043] The reduced viscosity in the present invention is a value calculated by measuring in dimethylformamide (DMF) at 25° C. and 1 g / dl using an Ubbelohde viscometer with reference to the method described in JIS K7367-1 (2002). In addition, the reduced viscosity (η sp / c, unit: dl / g) is calculated based on the following formula, and the average value of five measurements is used. η sp / c=(t-t0) / t0 / c (dl / g) t: Time (seconds) for a polymer solution to pass between the marks on a viscometer t0: Time (seconds) for a pure solvent to pass between the marks on a viscometer c: polymer solution concentration (g / dl)

[0044] The polyethersulfone resin used in the present invention may contain optional components such as a matting agent, a plasticizer, an antistatic agent, a coloring inhibitor, an antigelling agent, and a resin modifier, as needed, within the range that does not impair the properties of the resin. Furthermore, from the viewpoint of imparting desired performance while utilizing the inherent physical properties of the polyethersulfone resin, the polyethersulfone resin may be blended with at least one additive selected from a filler, a flame retardant, a colorant, a sliding property improver, an antioxidant, and a conductive agent.

[0045] The polyethersulfone resin used in the present invention is preferably melt-spun at a glass transition temperature (Tg) of 200°C or higher and 250°C or lower and a reduced viscosity of 0.30 dL / g or higher and 0.47 dL / g or lower. This allows the polyethersulfone fiber to be easily and stably produced without a drawing treatment. The temperature during melt spinning is preferably 340°C or higher and 410°C or lower. Polyethersulfone resins have a relatively high melt viscosity, which tends to generate shear heat during molding, affecting spinning conditions. Therefore, by having the glass transition temperature and reduced viscosity within the above ranges, a good balance between spinnability, heat resistance, and heat shrinkage is achieved.

[0046] [Melt spinning of polyethersulfone resin] Next, the melt spinning method of polyethersulfone resin will be described. The polyethersulfone resin obtained above, which has a glass transition temperature (Tg) of 200°C or higher and a reduced viscosity of 0.30 dL / g or higher and 0.47 dL / g or lower, is thoroughly dried to obtain a dried polyethersulfone resin meeting the following condition (a) (drying step). Thereafter, the dried polyethersulfone resin is heated and melted to obtain a melt (melting step). The melt is then extruded from a die to form fibers (spinning step). Furthermore, the spun yarns extruded from the spinneret are bundled to obtain filaments (bundling step). Finally, the filament is wound onto a tube (winding process). In this way, the polyethersulfone fiber of the present invention can be produced according to the following conditions (a) to (e). Condition (a): Moisture content of dry polyethersulfone resin is less than 50 ppm Condition (b): Linear velocity of discharge is 5.0 m / min or more and 50.0 m / min or less Condition (c): Shear rate during spinning is 300 s -1 More than 90,000s -1 below Condition (d): Spinning temperature is 340°C or higher and 410°C or lower Condition (e): Winding speed is 550 m / min or more The manufacturing method of the present invention is characterized in that it does not substantially involve a post-process drawing step of heating and drawing the bundled filaments. As a post-process, the bundled filaments may be further subjected to a heat treatment process by heating them at a temperature of 150° C. or higher and 300° C. or lower. Each step will be described in detail below.

[0047] (drying process) The polyethersulfone resin obtained above is stored in a vacuum dryer and dried for 10 to 30 hours at a temperature of 100 to 200°C. Since polyethersulfone resin is hygroscopic, it is preferable to dry it thoroughly. The moisture content of the polyethersulfone resin is preferably less than 50 ppm by a drying process, more preferably 30 ppm or less, and even more preferably 25 ppm or less, which can prevent the generation of bubbles during spinning. The dried polyethersulfone resin may be in the form of pellets or powder. Drying may be carried out under a nitrogen stream or by using a tumbler or the like to dry the resin under fluidized conditions. By making the water content of the dried polyethersulfone resin less than 50 ppm, it is possible to prevent gas generation due to moisture during melting, and to preferably prevent problems such as the inclusion of voids in the spun yarn and the generation of gel-like insoluble matter that makes stable spinning impossible. Between the drying step and the spinning step, an environment of 30°C or higher is preferably maintained, and 40°C or higher is more preferable, so as to prevent an increase in the moisture content of the polyethersulfone resin. The upper limit of the environment is preferably maintained at 80°C or lower. A nitrogen flow is also more preferable.

[0048] (Spinning process) The melt extrusion of the polyethersulfone resin in the present invention may be performed by any known method as long as it is suitable for melt spinning. For example, the polyethersulfone resin may be pelletized and melt extruded using an extruder-type extruder 1. FIG. 1 shows an example of a method for producing polyethersulfone fibers by melt-extruding a polyethersulfone resin from an extruder 1 and melt-spinning it. The molten resin extruded from the extruder 1 passes through piping and is sent to the spinning head, where it is metered by a known metering device such as a gear pump 2, passes through a filter in the spinning pack 3, and then enters the spinneret 3a.

[0049] The spinning temperature under condition (d) is the temperature of the molten resin from the gear pump 2 to the spinneret 3a, and is preferably 340°C or higher and 410°C or lower for the polyethersulfone resin. If the spinning temperature is lower than the lower limit, problems such as increased filtration pressure or overloading of the extruder may occur, while if it exceeds the upper limit, the quality of the fiber may deteriorate due to the effects of thermal decomposition. A more preferred spinning temperature in the present invention is 340°C or higher and 390°C or lower, and most preferably 345°C or higher and 375°C or lower. Because polyethersulfone resin has a high melt viscosity, the resin temperature tends to rise above the cylinder temperature setting due to shear heating. Therefore, it is preferable to check the resin temperature while molding. If the melt viscosity exceeds the upper limit, spinnability during melt spinning becomes poor, and if the melt viscosity falls below the lower limit, stable spinning becomes difficult.

[0050] The shear rate γ in the spinneret hole under condition (c) is 300 s -1 More than 90,000s -1 It is preferable to set it to 340s or less. -1 More than 60,000s -1 It is more preferable to set it to 5,000s or less. -1 More than 60,000s -1 It is more preferable that: The shear rate γ is calculated by the following formula: γ=4Q / πr 3 (where r is the radius of the spinneret hole (cm), Q is the polymer discharge amount per hole (cm 3 / sec)) When the shear rate γ is within the above range, the fibers are sufficiently oriented, making it easier to obtain fine fibers and achieve the desired physical properties. It is also preferable to set the residence time of the polyethersulfone resin to a short time, as a long residence time can cause thermal decomposition, resulting in an increase in melt viscosity and the generation of bubbles, which can deteriorate the quality of the fiber and cause yarn breakage.

[0051] The hole size D (diameter) of the spinneret 3a is preferably 0.09 mm or more and 0.70 mm or less, and more preferably 0.12 mm or more and 0.45 mm or less. In addition, by installing a heater and a heat-retaining tube directly below the spinneret 3a, the diameter of the extruded fiber can be stabilized, and changes in the surface temperature of the spinneret and the ambient temperature below the spinneret caused by outside air can be suppressed, resulting in uniform thinning by draft and stable spinning without thread breakage or fluffing.

[0052] The linear velocity of the spun fiber discharged from the spinneret 3a under condition (b) is preferably 5.0 m / min or more and 50.0 m / min or less, and more preferably 10.0 m / min or more and 40.0 m / min or less. The shear rate in the spinneret hole under condition (c) was 300 s -1 More than 90,000s -1 It is preferable to set it to 340s or less. -1 More than 60,000s -1 It is more preferable to set it to 5,000s or less. -1 More than 60,000s -1 It is more preferable that: The take-up speed (spinning speed) under condition (e) is preferably 550 m / min or more, more preferably 600 m / min or more, and even more preferably 650 m / min or more. In this case, the upper limit of the take-up speed is preferably 5,000 m / min or less, and more preferably 4,000 m / min or less. The ratio of the winding speed to the linear speed is preferably 40 times or more and 1,600 times or less. This allows high quality polyethersulfone fibers to be produced by melt spinning.

[0053] The heating in the bundling process, winding process, and post-process will be described in more detail below. (Focusing process) The spun yarn extruded from the spinneret 3a is coated with a predetermined oil in an oil application device and bundled into a single filament. The polyethersulfone fiber of the present invention is a filament, and may be either a monofilament or a multifilament. In the case of a multifilament, the number of single fibers is preferably 6 or more. If the number of single fibers is less than 6, the strength of the multifilament itself will be weak, making it difficult to wind the fiber in a satisfactory manner through the process, and yarn breakage and the like will be likely to occur, which may result in reduced productivity. The cross-sectional shape of each single yarn is not particularly limited, and it may be not only a round cross-section but also a modified cross-section depending on the purpose and application.

[0054] (winding process) The polyethersulfone fiber that has been converted into a filament through the bundling process is then taken up by a first godet roll 4 and a second godet roll 5 and wound onto a take-up bobbin 6. The take-up speed is preferably 550 m / min or more, more preferably 600 m / min or more, and even more preferably 650 m / min or more. The upper limit of the take-up speed is preferably 5,000 m / min or less, and more preferably 4,000 m / min or less. The spinning winding tension measured between the second godet roll 5 and the take-up bobbin 6 is preferably 4.7 cN or more and 47 cN or less. If the tension is less than 4.7 cN, the fibers may slacken, causing the yarn to wind around the second godet roll 5 or causing a defective shape of the take-up bobbin 6. In the present invention, the spinning winding tension indicates the tension measured when the yarn is wound around the take-up bobbin 6.

[0055] (Post-process: Heat treatment) The polyethersulfone fiber obtained as described above may be subjected to a heat treatment for a certain period of time, which may be carried out in an inert atmosphere such as nitrogen gas.

[0056] As described above, the polyethersulfone fiber of the present invention does not include a drawing treatment (drawing step) as a post-spinning process. By using a non-drawable PES fiber, entropy shrinkage does not occur even in high-temperature environments exceeding 100°C, and fiber shrinkage can be preferably prevented. In particular, because polyethersulfone resin is an amorphous thermoplastic resin, oriented crystals do not occur even when stretched or heat-treated. However, stretching increases dry heat shrinkage and reduces dimensional stability. The term "drawing treatment" as used herein refers to drawing the fibers to a length of 1.2 times or more, and does not include the operation of applying an appropriate tension to the fibers in the above-mentioned winding process.

[0057] (Physical properties of polyethersulfone fiber) The polyethersulfone fiber obtained as described above is preferably adjusted to have the following physical properties by adjusting the shear rate γ, hole diameter D, winding speed ratio, etc. That is, the polyethersulfone fiber obtained by melt spinning preferably has a total fineness of 30 dtex or more, more preferably 50 dtex or more, and a single fiber fineness of about 1 dtex to 12 dtex. The polyethersulfone fiber may be in the form of a monofilament or a multifilament, and in the case of a multifilament, the number of filaments is preferably 6 or more. The breaking strength of the polyethersulfone fiber is preferably 1.0 cN / dtex or more, more preferably 1.2 cN / dtex or more, and even more preferably 1.5 cN / dtex or more. Furthermore, the variation in breaking strength of the polyethersulfone fiber is preferably less than ±0.3 cN / dtex, and more preferably within ±0.2 cN / dtex. The breaking elongation of the polyethersulfone fiber is preferably 10% or more and 200% or less, more preferably 20% or more and 180% or less, and even more preferably 30% or more and 170% or less. This makes it possible to produce polyethersulfone fibers that are high in strength and also have excellent properties such as dimensional stability and thermal stability.

[0058] The dry heat shrinkage rate of the polyethersulfone fiber of the present invention at 200°C is 5% or less, preferably 4% or less, more preferably 3% or less, even more preferably 2% or less, and most preferably 1% or less. With a dry heat shrinkage rate of 5% or less, it can be used for a variety of industrial materials. In particular, because it has excellent dimensional stability even in high-temperature environments, it can be used for precision parts or products made or used in harsh environments. For example, when the fibers are used as a thermally adhesive conjugate fiber that is thermally fused to fix the fibers in the form of a nonwoven fabric, the thermally adhesive conjugate fiber has a problem that, due to differences in the properties of the composite resin components, large heat shrinkage occurs in the heat treatment step, causing the dense portions of the fibers to harden. By setting the dry heat shrinkage rate to the above upper limit or less, shrinkage and hardening of the nonwoven fabric can be prevented, dimensional stability is improved, and a high-quality nonwoven fabric can be obtained. The reduced viscosity of the resin constituting the polyethersulfone fiber is preferably 0.30 dL / g or more, which improves processability and allows for the production of high-quality fibers without the occurrence of thread breakage.

[0059] [Uses of polyethersulfone fiber] The polyethersulfone fibers of the present invention can be used for applications such as nonwoven fabrics, filters, ropes, etc. For example, they can be used as continuous fibers, knitted or woven into fabrics, or cut into short fibers to form nonwoven fabrics, and are useful as materials for heat-resistant clothing, heat insulating materials, heat-resistant filters, insulating paper stocks, etc. Furthermore, they have excellent electrical properties and can be used as electronic substrates. The polyethersulfone fiber of the present invention can be precisely processed due to its dimensional stability, and can be used in the fields of electric and electronic parts, automobiles, and medicine.Since it does not emit environmental hormones, it can also be used in the fields of medicine and food.

[0060] Furthermore, because the polyethersulfone fiber of the present invention has excellent processability, it can be mixed with multiple types of fibers to form a commingled fiber or processed into fiber-reinforced plastics. Furthermore, the polyethersulfone fiber of the present invention can be used as short fibers to form nonwoven fabrics, nonwoven fabric laminates, or fiber-reinforced plastics. Because of their excellent strength, processed products made from the polyethersulfone fiber thus obtained can be lightweight and can withstand harsh environments, making them suitable for applications in space, aviation, automobiles, and the like (structures, engine parts, etc.). Furthermore, the polyethersulfone resin of the present invention has excellent rigidity and dimensional stability over a wide temperature range, and also has excellent creep resistance at high temperatures, resistance to gasoline, gasohol, and engine oil, and sliding properties, making it suitable for use in the mechanical field. [Example]

[0061] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0062] <Measurement method for polyethersulfone resin> The properties in the examples were measured by the following methods. 1. Reduced viscosity (η sp / c) The reduced viscosity was measured using an Ubbelohde viscometer in dimethylformamide (DMF) at 25°C and 1 g / dl, in accordance with the description of JIS K7367-1 (2002). sp / c (unit: dl / g) was calculated based on the following formula, and the average value of five measurements was used. η sp / c=(t-t0) / t0 / c(dl / g) t: Time (seconds) for a polymer solution to pass between the marked lines on a viscometer t0: Time (seconds) for the pure solvent to pass between the marks on the viscometer c: polymer solution concentration (g / dl)

[0063] 2. Moisture content (ppm) Measurement was carried out using a Karl Fischer moisture meter (manufactured by Mitsubishi Chemical Corporation, Model VA-200).

[0064] 3. Strength, elongation, and strength variation In accordance with the standard test of JIS L1013 (2010), a Shimadzu AGS-500NX tensile tester was used to determine the breaking strength, elongation, and modulus of elasticity (initial tensile resistance) at a sample length of 200 mm and a tensile speed of 200 mm / min. The values ​​were expressed as the average of 10 points, and the strength, elongation, and strength variation were measured.

[0065] 4. Glass transition temperature (Tg) Measurements were performed using a differential scanning calorimeter (DSC-6220, manufactured by SII NanoTechnology, Inc.). The polyethersulfone resin was subjected to a thermal history under a nitrogen atmosphere. The thermal history conditions were a first heating (heating rate: 10°C / min), followed by cooling (cooling rate: 20°C / min), and then a second heating (heating rate: 10°C / min).

[0066] <Evaluation method for polyethersulfone fiber> 5. Evaluation of spinning status The spinning state after spinning for 2 hours or more was evaluated as follows. ○: Stable spinning was possible without any yarn breakage. △: Yarn breakage occurred during 2 hours of spinning. (Air bubbles: Although winding is possible, bubbles that appear directly below the nozzle are thought to be caused by resin deterioration, leading to thread breakage and uneven strength.) Unable to wind: Frequent thread breakage prevented winding (thread breakage due to resin deterioration or increased filtration pressure). Unable to spin: It was not possible to wind the yarn in the first place.

[0067] 6.Dry heat shrinkage rate The dry heat dimensional change rate (%) at 200°C was determined according to JIS L1013 (2010) 8.18.2 b) Filament dimensional change rate (Method B).

[0068] Example 1 <Polyethersulfone resin melt spinning process> As the polyethersulfone resin, Sumikaexcel (registered trademark) 3600G (manufactured by Sumitomo Chemical Co., Ltd.) was used. This polyethersulfone resin had a glass transition point of 225° C. and a reduced viscosity of 0.36 dl / g.

[0069] The chips were dried for 20 hours in a vacuum dryer at 160° C. The moisture content was 20 ppm or less (drying step). The obtained dried chips were melt-extruded while being heated using an extruder 1, and the melt-extruded resin was metered using a gear pump 2 and supplied to a spinning pack 3 (melting step). The spinning temperature was set to 360°C, and the mixture was extruded from the spinneret 3a to form fibers. The number of spinneret holes was 24, and the linear velocity during extrusion from the spinneret 3a was 11.2 m / min, and the shear rate γ was 5931 s -1 (spinning process).

[0070] The spun yarn extruded from the spinneret 3a was treated with an oil when it solidified, and then collected into a single multifilament 30 cm below the spinneret (collecting process). The collected yarn was then wound onto a paper tube using a winder at a winding speed (spinning speed) of 650 m / min to obtain a polyethersulfone fiber of 260 dtex / 24 f (winding process). The physical properties and spinnability evaluation results are shown in Table 1.

[0071] Example 2 Polyethersulfone fibers were obtained in the same manner as in Example 1, except that chips of Sumikaexcel (registered trademark) 4100G (manufactured by Sumitomo Chemical Co., Ltd.) were used as the polyethersulfone resin and the spinning conditions were as shown in Table 1. The polyethersulfone resin of Example 2 had a glass transition temperature of 225° C. and a reduced viscosity of 0.43 dl / g. Example 3 Polyethersulfone fibers were obtained in the same manner as in Example 1, except that the spinning conditions were as shown in Table 1.

[0072] Example 4 Polyethersulfone fibers were obtained in the same manner as in Example 1, except that the spinning conditions were as shown in Table 1. Example 5 Polyethersulfone fibers were obtained in the same manner as in Example 1, except that the spinning conditions were as shown in Table 1.

[0073] (Comparative Example 1) Spinning was carried out in the same manner as in Example 1, except that chips of Sumikaexcel (registered trademark) 4800G (manufactured by Sumitomo Chemical Co., Ltd.) were used as the polyethersulfone resin and the spinning conditions were as shown in Table 1. The polyethersulfone resin of Comparative Example 1 had a glass transition temperature of 225° C. and a reduced viscosity of 0.48 dl / g. In Comparative Example 1, although spinning was possible, the fiber was in poor condition and many thread breaks occurred, making it impossible to wind the fiber.

[0074] (Comparative Example 2) The same procedure as in Example 1 was carried out except that the spinning conditions were as shown in Table 1. In Comparative Example 2, the resin viscosity was high due to the low spinning temperature, and the gear pump 2 (GP) was overloaded and broke down, making spinning impossible.

[0075] (Comparative Example 3) Spinning was carried out in the same manner as in Example 1, except that the moisture content of the polyethersulfone resin chips was set to 60 ppm and the spinning conditions were as shown in Table 1. In Comparative Example 3, although spinning was possible, the moisture content was not appropriate, and many bubbles were generated in the fiber, resulting in poor fiber condition and making it impossible to wind up.

[0076] Comparative Example 4 After spinning in the same manner as in Example 1, the yarn was stretched as follows. That is, the polyethersulfone fiber taken up in the winding step was wound around a roller, unwound, and introduced into a roll heater heated to 150°C, where it was drawn at a draw ratio of 1.7 times and then taken up.

[0077] (Comparative Example 5) After spinning in the same manner as in Example 1, the yarn was stretched as follows. That is, the polyethersulfone fiber wound in the winding step was wound around a roller, unwound, and introduced into a roll heater heated to 150°C, where it was stretched at a draw ratio of 2.0, and then wound up.

[0078] (Comparative Example 6) Spinning was carried out in the same manner as in Example 1, except that chips of Ultrason (registered trademark) E1010 (manufactured by BASF) were used as the polyethersulfone resin and the spinning conditions were as shown in Table 1. The polyethersulfone resin of Comparative Example 6 had a glass transition temperature of 222°C and a reduced viscosity of 0.48 dl / g. In Comparative Example 6, although spinning was possible, the fiber was in poor condition and many thread breaks occurred, making it impossible to wind the fiber.

[0079] (Comparative Example 7) Spinning was carried out in the same manner as in Example 1, except that chips of Ultrason (registered trademark) E2010 (manufactured by BASF) were used as the polyethersulfone resin and the spinning conditions were as shown in Table 1. The polyethersulfone resin of Comparative Example 7 had a glass transition temperature of 225° C. and a reduced viscosity of 0.56 dl / g. In Comparative Example 7, although spinning was possible, the fiber was in poor condition and many thread breaks occurred, making it impossible to wind the fiber.

[0080] [Table 1]

[0081] [Table 2]

[0082] The results in Tables 1 and 2 confirm that the polyethersulfone fibers of Examples 1 to 5 had a dry heat shrinkage of 5% or less, a breaking strength of 0.6 cN / dtex or more, a breaking strength variation of ±0.3 cN / dtex or less, and an elongation of 10% or more but less than 200%. The resulting fibers were bundled and cut, then passed through a papermaking process and calendered to produce nonwoven fabrics. The polyethersulfone fibers obtained in Examples 1 to 5 were easy to pass through the processes, and the resulting nonwoven fabrics had good dimensional stability.

[0083] Furthermore, the polyethersulfone fibers of Examples 1 to 3 were excellent fibers with high breaking strength of 1.0 cN / dtex or more and little variation in strength. It was also confirmed that the polyethersulfone fibers obtained in Examples 1 to 3 had superior post-processing passability and dimensional stability. The fibers obtained in Examples 1 and 2 were particularly excellent in post-processing passability and dimensional stability.

[0084] On the other hand, in Comparative Examples 1 to 7, spinning was not possible, or even if spinning was possible, the fiber was in such a bad state that winding was not possible. In Comparative Examples 4 and 5, even if winding was possible, the dry heat shrinkage was poor, and there were problems with post-processing and dimensional stability. When the fibers obtained in Comparative Examples 4 and 5 were subjected to calendering, the processability was poor and the dimensional stability of the nonwoven fabric was also poor. [Explanation of symbols]

[0085] 1. Extruder 2 gear pumps 3 Spinning Pack 3a Spinneret 4. First Godet Roll 5 Second Godet Roll 6. Take-up bobbin

Claims

1. The polyethersulfone resin comprises a repeating unit represented by the following formula (1): A polyethersulfone fiber having a dry heat shrinkage rate of 5% or less at 200°C. 【Chemistry 1】

2. 2. The polyethersulfone fiber according to claim 1, wherein the polyethersulfone resin contains 95 mol % or more of the repeating unit represented by formula (1).

3. 3. The polyethersulfone fiber according to claim 1, wherein the polyethersulfone resin has a glass transition temperature (Tg) of 200° C. or higher and a reduced viscosity of 0.30 dl / g or higher and 0.47 dl / g or lower.

4. 4. The polyethersulfone fiber according to claim 1, having at least one physical property selected from the group consisting of the following physical properties (A), (B), and (C): Physical property (A): The breaking strength of the polyethersulfone fiber is 0.6 cN / dtex or more. Physical property (B): The variation in breaking strength of the polyethersulfone fiber is within ±0.3 cN / dtex. Physical property (C): The elongation of the polyethersulfone fiber is 10% or more but less than 200%.

5. 5. The polyethersulfone fiber according to claim 4, wherein, in the physical property (A), the polyethersulfone fiber has a breaking strength of 1.0 cN / dtex or more.

6. A fiber package comprising the polyethersulfone fiber according to any one of claims 1 to 5 wound around a tube.

7. A nonwoven fabric comprising the polyethersulfone fiber according to any one of claims 1 to 5.

8. a drying step of drying the polyethersulfone resin to obtain a dried polyethersulfone resin; a melting step of heating and melting the dried polyethersulfone resin to obtain a melt; a spinning step of extruding the molten material from a spinneret to form fibers; a bundling step of bundling the spun yarns to obtain filaments; and a winding step of winding the filament; A method for producing polyethersulfone fibers, comprising: A method for producing polyethersulfone fibers that satisfies the following conditions: Condition (a): The moisture content of the dried polyethersulfone resin is less than 50 ppm. Condition (b): Linear velocity of extrusion is 5.0 m / min or more and 50.0 m / min or less Condition (c): Shear rate during spinning is 300 s -1 More than 90,000s -1 below Condition (d): Spinning temperature is 340°C or higher and 410°C or lower Condition (e): Winding speed is 550 m / min or more

9. 9. The method for producing polyethersulfone fibers according to claim 8, wherein the polyethersulfone resin has a glass transition temperature (Tg) of 200°C or higher and a reduced viscosity of 0.30 dl / g or higher and 0.47 dl / g or lower.

10. 10. The method for producing polyethersulfone fibers according to claim 8 or 9, wherein under the condition (d), the spinning temperature is 340°C or higher and 385°C or lower.